Determinants of Skill Levels in Paediatric Emergency Management among Primary Healthcare Workers - Suberu PO; Obohwemu KO; Soyobi VY; Yakpir MG; Henry K; Ndioho I (Medical Science: Trends and Innovations Vol. 6, 2025)
Background: Paediatric emergencies remain a significant public health concern in Nigeria, especially in rural areas where primary healthcare centres (PHCs) often serve as the sole source of medical care. The ability of healthcare workers in these settings to effectively manage paediatric emergencies is crucial for improving child health outcomes. Objective: This study aimed to assess the determinants of skill levels in paediatric emergency management among primary healthcare workers in Zaria, Nigeria. This study underscores the critical need for targeted interventions to improve the skills of primary healthcare workers in managing paediatric emergencies in Zaria, Nigeria. Methods: A cross-sectional descriptive study was conducted among 139 randomly selected healthcare workers in Sabon Gari and Zaria Local Government Areas. Data were collected using a pre-tested questionnaire that included socio-demographic characteristics, work experience, and skills in managing paediatric emergencies. Data analysis was performed using SPSS version 21. Descriptive statistics and chi-square tests were employed to analyze the data. Results: The results revealed that healthcare workers in PHCs in Zaria exhibited varying levels of skills in managing paediatric emergencies. Several determinants were identified as influencing their skill levels. Healthcare workers with higher academic qualifications demonstrated significantly better skills in managing paediatric emergencies, suggesting that formal education plays a crucial role in developing the necessary competencies. While experience can be a valuable asset, the study did not find a strong association between years of experience and skill levels, indicating that experience alone is not sufficient for developing the necessary skills. Additional training and support may be required. The training and mentorship programs provide structured support and continuous learning opportunities, which are particularly beneficial in resource-limited settings. Healthcare workers who had received recent training or participated in continuing medical education (CME) programs related to paediatric emergency management tended to have higher skill levels, highlighting the importance of ongoing professional development. Conclusion: The findings of this study suggest that a combination of determinants influences the skill levels of primary healthcare workers in managing paediatric emergencies. While academic qualifications are important, ongoing training and access to resources are also essential. It is crucial to address these determinants through targeted interventions to improve the skills of healthcare workers and enhance the quality of care provided to children in need. This study underscores the critical need for targeted interventions to improve the skills of primary healthcare workers in managing paediatric emergencies in Zaria, Nigeria. By addressing factors such as academic qualifications, training, resource availability, and work environment, policymakers and healthcare providers can significantly enhance the quality of care provided to children in need.